Structure-property relationship of Cu-Al-Ni-Fe shape memory alloys in different quenching media - Saud, Safaa Najah (Springer, 2014)
This paper presents the effects of heat treatments using various quenching media on the phase transformation parameters and microstructure parameters. The effects of different quenching methods, step-quenched and up-quenched, in various media were evaluated by using differential scanning calorimetry, field emission electron microscopy, energy-dispersive spectrometry, atomic force microscopy, x-ray diffraction, and Vicker's hardness. The variations of the structure and properties of Cu-Al-Ni-Fe shape memory alloys were linked to the variations of morphology, type, and stabilization of the obtained phase. From the DSC results, the use of ice water as a quenching medium produced the highest transformation temperatures, while a brine solution-quenching medium resulted in the highest change of the entropy and enthalpy. Additionally, it was found that the best grain refinement was observed through the use of an oil-quenching medium, due to its high cooling rate.